Heat Shock Protein HSP27 Secretion by Ovarian Cancer Cells Is Linked to Intracellular Expression Levels, Occurs Independently of the Endoplasmic Reticulum Pathway and HSP27's Phosphorylation Status, and Is Mediated by Exosome Liberation. (23rd February 2017) - Stope, Matthias B.; Klinkmann, Gerd; Diesing, Karoline; Koensgen, Dominique; Burchardt, Martin; Mustea, Alexander
Abstract : The heat shock protein HSP27 has been correlated in ovarian cancer (OC) patients with aggressiveness and chemoresistance and, therefore, represents a promising potential biomarker for OC diagnosis, prognosis, and treatment response. Notably, secretion of soluble HSP27 has been described by a few cell types and may take place as well in OC cells. Therefore, we studied HSP27 secretion mechanisms under diverse cellular conditions in an OC cell model system. Secretion of HSP27 was characterized after overexpression of HSP27 by transfected plasmids and after heat shock. Intra- and extracellular HSP27 amounts were assessed by Western blotting and ELISA. Protein secretion was blocked by brefeldin A and the impact of the HSP27 phosphorylation status was analyzed overexpressing HSP27 phosphomutants. The present study demonstrated that HSP27 secretion by OVCAR-3 and SK-OV-3 cells depends on intracellular HSP27 concentrations. Moreover, HSP27 secretion is independent of the endoplasmic reticulum secretory pathway and HSP27 phosphorylation. Notably, analysis of OC cell-born exosomes not only confirmed the concentration-dependent correlation of HSP27 expression and secretion but also demonstrated a concentration-dependent incorporation of HSP27 protein into exosomes. Thus, secreted HSP27 may become more important as an extracellular factor which controls the tumor microenvironment and might be a noninvasive biomarker.